Effect of apparatus characteristics on anxiety-like behavior in young adult and old mice of both sexes assessed by the elevated plus maze assay - Gaspar, Lauren; Bartman, Sydney; Coppotelli, Giuseppe; Ross, Jaime M. (Frontiers in Behavioral Neuroscience, 2023)
Incidence of anxiety-like disorders in humans has been shown to decrease with aging; however, it is still under debate whether there are similarities in mice, which would support the use of mouse models in understanding the neuronal network changes that regulate anxiety-like behavior in aging. One of the most common tests used to assess anxiety-like behavior in laboratory animals is the elevated plus maze (EPM). Although several variables, such as room brightness and width of the maze arms, have been shown to influence the spontaneous animal behavior during the EPM test, none of these variables have ever been evaluated in aging to understand their possible differential effect on younger and old mice. We therefore decided to investigate the effect of apparatus construction on young adult and old mice of both sexes on EPM test performance. Our results show that distance traveled during the test is the variable that is most affected by apparatus characteristics independent of age and sex. We also found that apparatus construction was key in demonstrating that old mice spent more time and had relatively more entries in the open arms as compared to young mice, suggesting a decrease in anxiety-like behavior with age. Taken together, our data demonstrate that EPM apparatus characteristics affects dramatically test outcome with a wider arm apparatus being more effective in revealing age-dependent changes in anxiety-like behavior, thus, suggesting the use of a wider arm EPM when conducting aging studies in mice.